2012
DOI: 10.1088/1751-8113/45/38/385302
|View full text |Cite
|
Sign up to set email alerts
|

$\mathcal {PT}$-symmetric non-commutative spaces with minimal volume uncertainty relations

Abstract: We provide a systematic procedure to relate a three dimensional q-deformed oscillator algebra to the corresponding algebra satisfied by canonical variables describing noncommutative spaces. The large number of possible free parameters in these calculations is reduced to a manageable amount by imposing various different versions of PTsymmetry on the underlying spaces, which are dictated by the specific physical problem under consideration. The representations for the corresponding operators are in general non-H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 46 publications
6
80
0
Order By: Relevance
“…We demonstrated that all key requirements for coherent states are satisfied. A direct comparison with the results obtained in [5] is not possible as the analysis in there relates to a nontrivial limit q → 1, which is not directly obtainable from the setting presented here, see [1,4]. However, qualitatively we found a somewhat different behaviour with regard to the key question addressed in this manuscript.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We demonstrated that all key requirements for coherent states are satisfied. A direct comparison with the results obtained in [5] is not possible as the analysis in there relates to a nontrivial limit q → 1, which is not directly obtainable from the setting presented here, see [1,4]. However, qualitatively we found a somewhat different behaviour with regard to the key question addressed in this manuscript.…”
Section: Discussionmentioning
confidence: 54%
“…Let us now investigate some properties of these states and in particular investigate to which kind of expectation values they lead for observables and compare with the results for the nontrivial q → 1 limit studied in [5]. In the latter case these states were found to be squeezed states up to first order in perturbation theory in τ when parameterizing the deformation parameter as q = e 2κ 2 6 τ , where κ 6 is explained in [4]. Most importantly we wish to investigate whether these states respect the generalized uncertainty relations.…”
Section: Generalized Time-dependent Q-deformed Coherent Statesmentioning
confidence: 92%
See 2 more Smart Citations
“…More interesting structures, leading for instance to minimal length and generalized versions of Heisenberg's uncertainty relations, are obtained when θ µν is taken to be a function of the momenta and coordinates, e.g. [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%